A Case Report Illustrating the Spontaneous Vision Recovery After Inadvertent Central Descemetorhexis During Anterior Capsulotomy - Baráková, Drahomíra; Darsová, Denisa (International medical case reports journal, 2021)
Purpose: To demonstrate an unusual mechanism of iatrogenic, central descemetorhexis (DMR) during cataract surgery and subsequent rare spontaneous visual acuity improvement within 2 months after inadvertent surgical complication. Patients and Methods: A 81 year old woman underwent cataract surgery complicated by the loss of a 4.8X4.75 mm diameter central area of Descemet membrane. Perioperative video recording documented the DMR formation during continuous curvilinear capsulorhexis creation. Results: Postoperatively, severe corneal edema with folds in the remaining Descemet membrane were observed. The patient was managed conservatively. The corneal edema gradually resolved over 2 months with improving of visual acuity from counting fingers to 20/20. Conclusion: Unlike Descemet membrane detachment, descemetorhexis is a rare complication after intraocular surgery. The case report identifies a previously unknown mechanism of DMR formation during anterior capsulotomy creation. Loss of Descemet membrane may be managed conservatively in an otherwise healthy cornea with good final visual outcome without the need for surgical intervention.